Natural School Curriculum Study In Order To Prevent Educational Character Education Basic School Level - Yulianti Yulianti (STAI Miftahul Ula Nganjuk, 2017)
The curriculum and learning are two things that can not be separated. As a plan or program, the curriculum will not be meaningful when it is not implemented in the form of learning. And vice versa, without a clear curriculum as a reference, then learning will not take place effectively (Sanjaya: 2009). What is described in the curriculum should provide clues to the learning process in the classroom; And what happens in the classroom is an input that can be taken into consideration in the improvement of the curriculum. Elementary School Islam (SDI) Surya Buana Malang one of the primary schools in the city of Malang that has a different character from another school Dinas. This study aims to find out and describe what the concept of natural school in SD Surya Buana Malang and how its implementation in realizing the character education of elementary school students. The research method used is qualitative research method. This study used a qualitative approach with an observational case study research design related to the concept of curriculum development of SDI Bilingual School SDI Surya Buana Malang. Data collection techniques are (1) in-depth interview (2) participant observation and (3) documentation study. Data analysis used in this research: data reduction, data presentation, and conclusion or verification. The result of the research shows that Islamic elementary school of SDI Surya Buana Malang apply curriculum of Diknas by applying the concept of the curriculum of natural school